Transcription of DNA from the 70S RNA of Rous Sarcoma Virus I. Identification of a Specific 4S RNA Which Serves as Primer - Dahlberg, J. E. (1974)
The enzymatic transcription of DNA from the 70S RNA of Rous sarcoma virus (RSV) is initiated on the 3′ terminus of a molecule of 4S RNA which is hydrogen bonded to the viral genome. We labeled this primer with radioactive deoxynucleotides, and demonstrated that its release from 70S RNA by thermal denaturation was accompanied by a reduction in the template activity of the viral RNA. Two-dimensional electrophoresis in polyacrylamide gels separated the 4S RNAs associated with the 70S RNA of RSV into approximately eight fractions, each of which appeared to contain a discrete species of tRNA. The RNA in one of these fractions served as the principal primer for initiation of DNA synthesis by both detergent-disrupted virions of RSV and purified RNA-directed DNA polymerase with RSV 70S RNA as template.